Characteristics of the brood stock of Nesvych intrabreed type of Ukrainian framed and scaly breeds of carp based on the complex of productive and reproductive parameters - H. Kurinenko; Yu. Chernyk; U. Kuts; I. Hrystyniak; S. Yurchak; L. Bobeliak; V. Bekh (Ribogospodarsʹka Nauka Ukraïni, 2024)
Purpose. To provide an assessment of the complex of productive and reproductive parameters of the brood stock of the Nesvych intrabreed type of Ukrainian framed and scaly breeds of carp grown in pond conditions of the Polissia zone.